Silvia Baron Supervielle, une œuvre humaniste, entre deux langues, entre deux rives - Morello, André-Alain (Romanica Silesiana, 2025)
Silvia Baron Supervielle’s work brings an original voice to contemporary French and Francophone literature. The work of this writer, born in Argentina but living in France and writing in French, is that of a nomad who has never been uprooted. Her work not only constructs dialogues between two languages, between two continents, but also between poets and painters, between words and photographs, between prose and poetry. Indeed, it is part of the exploration for new forms of poetic novels, autobiographical texts and essay collections. Finally, this work is a great humanist endeavour which, built on the absence of the mother, celebrates fidelity and love.